Pembangunan Tamadun Islam akan berulang?: meneliti novel remaja 1511h [Kombat] karya Faisal Tehrani. - Misran Rokimin, (Universiti Kebangsaan Malaysia, 2009)
This article analyse an adolescent’s novel entitled 1511H (Combat) written by Faisal Tehrani a prolific young writer in Malaysia. Many of his works have touched on the importance of religious awareness amongst the young as a basis for their inner strength. The cyclical theory of history introduced by Ibn Khaldun more than 600 years ago is used to analyse the novel. This theory postulates that the development of the nation’s civilisation will rise and fall repetitively as a result of various conflicts. To sustain a nation’s civilisation and avoid potential collapse, Ibn Khaldun suggest that every citizen should have a strong sense of belonging based on good moral behaviour, obedience to work and duty, possess higher religious awareness and practice justice in managing and caring. The method used to analyse the novel is close reading technique, followed by content analysis of the novel by applying the four virtues mentioned to the main characters. It is hoped that the result of the analysis will help the Malays who had bitter experiences since the fall of Malacca Sultanate, through to the colonisation era of more than 400 years. Their re-emergence after independence on 31 August 1957 is a landmark. However, after 52 years of independence, signs of decay and fall can be seen especially after the 12th general election on 8 March 2008. The questions raised are whether the sense of belonging amongst the Malay/Islam have faded as viewed by Ibn Khaldun? Or is it possible the Malay/Islam will re-emerge with a solid sense of belonging in the year 2083 as portrayed in the novel? These questions will be the focus of the discussion.